The art front: the defense of French collections 1939-1945 - Valland, Rose (Laurel, 2024)
"In "The Art Front: The Defense of French Collections 1939-1945," French Monuments Woman Rose Valland recounts her experience spying on the Nazi looting operation at the Jeu de Paume during the four-year occupation of Paris and details the efforts of French fine arts and museum officials to safeguard their country's cultural heritage during World War II. Originally published in French as "Le front de l'art: Défense des collections françaises 1939-1945" (1961), "The Art Front" is the first English edition of Valland's memoir, made accessible to readers worldwide through the Monuments Men and Women Foundation's continued mission to honor the legacy of these scholar-soldiers. Translated by Ophélie Jouan, Rose Valland expert and art historian, and with a foreword by Robert M. Edsel, founder and chairman of the Monuments Men and Women Foundation and world-leading expert on the Monuments Men and Women, this edition features 105 illustrations, including color plates"--